2000
DOI: 10.1007/s003840050008
|View full text |Cite
|
Sign up to set email alerts
|

Fecal continence after rectocele repair: a prospective study

Abstract: Combined transvaginal/transanal rectocele repair was performed in series of 89 consecutive women (mean age 55, range 35-81 years) with obstructed defecation due to a rectocele with a depth of more than 3 cm. The impact of this procedure on anal sphincter pressure and continence status was evaluated prospectively. Anorectal manometry was carried out before and after surgery (at 3, 6, 12, and 24 months). The following measurements were performed: maximal anal resting pressure (MARP), maximal anal squeeze pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 15 publications
5
46
1
1
Order By: Relevance
“…Mean anal resting pressure was 77 mmHg (SD=7 mmHg) and mean squeeze pressure was 89 mmHg (SD=8 mmHg). No alteration of RAIR was reported; no sign of anismus was founded at balloon expulsion test [13][14][15][16][17][18]. Defecography showed presence and depth of rectocele barium trapping on postevacuation radiography in all cases; mean size of rectocele in these patients at defecography measurements (base x depth) was 4.8 cm x 4.3 cm (range: base, 3.5-6.5 cm; depth, 3-6 cm) ( Table 1).…”
Section: Methodsmentioning
confidence: 85%
“…Mean anal resting pressure was 77 mmHg (SD=7 mmHg) and mean squeeze pressure was 89 mmHg (SD=8 mmHg). No alteration of RAIR was reported; no sign of anismus was founded at balloon expulsion test [13][14][15][16][17][18]. Defecography showed presence and depth of rectocele barium trapping on postevacuation radiography in all cases; mean size of rectocele in these patients at defecography measurements (base x depth) was 4.8 cm x 4.3 cm (range: base, 3.5-6.5 cm; depth, 3-6 cm) ( Table 1).…”
Section: Methodsmentioning
confidence: 85%
“…This can be attributed both to the reduced time of surgical procedure and also the minimal anal divulsion produced by the use of CAD 33 (36 mm) compared with Park's rectal retractor (which has been associated with transient sphincteric impairment). 37 …”
Section: Discussionmentioning
confidence: 99%
“…This group of patients might not benefit from rectocele repair alone in terms of their symptoms related to hemorrhoids. However, transanal repair may compromise anal sphincter pressure, although it is not considered to cause severe fecal incontinence postoperatively [11, 25, 26]. Other studies have not demonstrated any significant reduction of anal sphincter pressure [2, 11, 13, 16, 19], although a few have noted a reduction of threshold volume and/or rectal compliance [2, 11].…”
Section: Discussionmentioning
confidence: 99%
“…The use of these physiologic investigations would be certainly advisable for comprehensive assessment of anorectal functional disorders. It is generally accepted that surgery for rectocele does not affect anal sphincter function as measured by manometry [1,2,3, 11, 12], though van Dam et al [26] reported a risk of impaired fecal continence after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation